Historia de mujeres y mujeres en la historia: evolución, contribución, retos y relevancia (Debates) - Banerjee, Ishita (2019)
This essay provides an overview of the ‘history of women/about women’ by drafting an account of this history as a separate and valid current in the field of history in the 1950s and 1960s consistent with important developments in social history. It briefly investigates the precursors of ‘women’s history,’ examines the emphases and distinctive contributions made by this school of thought, and explores its principal intersections with feminist theory and politics. It also examines the subsequent emergence of gender perspectives and post-colonial studies.